Knowledge, Attitude, and Practice of Physicians Regarding Vaccinations in Yerevan, Armenia: A Case Study of HPV - Arman R. Badalyan; Marine Hovhannisyan; Gayane Ghavalyan; Mary M. Ter-Stepanyan; Rory Cave; Jennifer Cole; Andrew W. K. Farlow; Hermine V. Mkrtchyan (Vaccines, 2021)
This paper highlights the low levels of vaccine coverage and high levels of reported vaccination hesitancy in Yerevan, Armenia, that present profound challenges to the control of disease through routine vaccination programmes. We draw on investigations of hesitancy towards the introduction of new vaccines, using the Human Papillomavirus (HPV) vaccine Gardasil as a case study, to interrogate underlying challenges to vaccine acceptance. We analyse primary data from the introduction of Gardasil, first used in Armenia in 2017, to investigate how levels of medical knowledge amongst physicians in 20 health facilities in Yerevan, Armenia, regarding vaccine science influence attitudes towards the introduction of a newly developed vaccine. A questionnaire-based cross-sectional study was completed by 348 physicians between December 2017 and September 2018. The responding physicians displayed a respectable level of knowledge and awareness regarding vaccination with respect to some characteristics (e.g., more than 81% knew that HPV infection was commonly asymptomatic, 73% knew that HPV infection was implicated in most cervical cancers, and 87% knew that cervical cancer is the most prevalent cancer amongst women) but low knowledge and poor understanding of other key issues such as the age at which women were most likely to develop cervical cancer (only 15% answered correctly), whether or not the vaccine should be administered to people who had already been infected (27% answered correctly) and whether sexually active young people should be treated for infection before vaccination (26% answered correctly). The study suggests that the drivers of vaccine hesitancy are complex and may not be consistent from vaccine to vaccine. The Armenian healthcare sector may need to provide additional training, awareness-raising and educational activities alongside the introduction of new vaccines to improve understanding of and trust in vaccination programmes.